Functional reduction of SK3-mediated currents precedes AMPA-receptor-mediated excitotoxicity in dopaminergic neurons - Benitez, Bruno A. (2011)
In primary cultures of mesencephalon small-conductance calcium-activated potassium channels (SK) are expressed in dopaminergic neurons. We characterized SK-mediated currents (ISK) in this system and evaluated their role on homeostasis against excitotoxicity. ISK amplitude was reduced by the glutamatergic agonist AMPA through a reduction in SK channel number in the membrane. Blockade of ISK for 12 h with apamin or NS8593 reduced the number of dopaminergic neurons in a concentration-dependent manner. The effect of apamin was not additive to AMPA toxicity. On the other hand, two ISK agonists, 1-EBIO and CyPPA, caused a significant reduction of spontaneous loss of dopaminergic neurons. 1-EBIO reversed the effects of both AMPA and apamin as well. Thus, ISK influences survival and differentiation of dopaminergic neurons in vitro, and is part of protective homeostatic responses, participating in a rapidly acting negative feedback loop coupling calcium levels, neuron excitability and cellular defenses.